Systematic & Complete Land Registration Effectiveness in Reducing Land Disputes in Kendari City - A. Hasdian Ikawati (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The importance of systemic and complete land registration in its development has not been able to materialize effectively, this has resulted in widespread problems of land ownership disputes in the community. The writing of this article uses an empirical juridical method. Based on existing research, it can be seen that the implementation of a complete and systemic registration is important in preventing land disputes. However, this has not been effective due to the problem of overlapping regulations and the problem of people's perspectives who still do not understand the importance of land registration at this time. So that the efforts made to overcome the obstacles that arise in the implementation of land registration are by providing legal counseling to the community, so that residents get sufficient legal information and knowledge to support the implementation of proper land registration. For the payment of BPHTB (Land Rights Acquisition Fee) for residents who cannot afford to have received relief in the payment.